Optimizing the Luring Period of Protein and Food Baits for Melon Fly (Zeugodacus cucurbitae Coquilette) Management - Jakkanagoudra, Manikantha B; Kavitha, Zadda; Shanthi, M.; Vijayaraghavan, C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Backgrounds: This study was carried out to determine the effective duration of protein and food baits in field traps for maximizing melon fruit fly captures. As protein and food baits trap both male and female fruit flies, employing these traps in field conditions is considered as a reliable alternate management strategy. Aim of the Work: Determination of trap placement periods in field conditions for maximum trap catches of melon fruit flies. Methodology: Olfactometer bioassays were conducted to assess the persistence of bait attractiveness. Changes in pH and protein content of baits were monitored over time. Results: Proteinex bait showed peak attraction between I–X days after preparation (DAP), while soybean bait was most effective from I–IX DAP. Tomato bait attracted the highest number of fruit flies at XII–XII DAP, and banana bait showed maximum attraction at I–VIII DAP. Protein baits had higher pH and protein content, correlating with their superior trap efficacy. Conclusion: For effective melon fly management, proteinex and soybean baits should be replaced every 10–12 days, tomato baits every 13 days, and banana baits every 8 days. The higher pH and protein content of protein baits contributed to their greater effectiveness, making them a valuable tool in sustainable pest control strategies.